23. TỔNG QUAN ĐẶC ĐIỂM DỊCH TỄ HỌC VÀ LÂM SÀNG BỆNH VIÊM NÃO MÀNG NÃO NGUYÊN PHÁT DO AMÍP Naegleria fowleri (Tạp chí Y học Cộng đồng, 2025)
Naegleria fowleri (N. fowleri) is a brain-eating amoeba that causes primary amebic meningoencephalitis (PAM). N. fowleri is found in freshwater, it enters the human body through the nasal passage migrating into the brain, which causes severe inflammation and destruction of brain tissue. From 1937 to 2018, 381 cases of PAM were reported globally, with the United States having the highest number of cases [1]. In Vietnam, medical literature recorded the first case of PAM in 2012 in a 25-year-old man with a history of exposure to freshwater through pearl diving in a natural lake in the Central region, admitted to the Hospital for Tropical Diseases in Ho Chi Minh City with symptoms of fever, headache, decreased consciousness and stiff neck. Lumbar puncture revealed the presence of leukocytes with a predominance of neutrophils, increased protein, decreased glucose, and numerous amoebas on wet mount microscopy. PCR testing of the 18s RNA target gene identified the causative agent as N. fowleri [2]. About a month later, in Ho Chi Minh City, a second case appeared in a 6-year-old boy with mental and motor developmental delay who had a brain abscess. The brain tissue sample was sent by the forensic agency for PCR testing to confirm the death was caused by N. fowleri causing a brain abscess. In 2024, Ho Chi Minh City Children's Hospital 1 recorded a case of brain-eating amoeba in a 10-month-old child admitted to the hospital on the 3rd day with high fever, vomiting, and lethargy. PCR testing of the cerebrospinal fluid found N. fowleri with a count of 3.3x107 copies/mL [3]. PAM presents with symptoms similar to bacterial meningitis, making initial diagnosis difficult. Treatment involves a combination of pharmacotherapy and supportive care. In Vietnam, PAM caused by N. fowleri is rare and not well known. This review highlights the genetic diversity, advances in diagnosis, and effective treatments for N. fowleri.
Keywords: Naegleria fowleri; viêm não màng não do amíp nguyên phát; dịch não tủy